Clinical and neuroradiological differences of paediatric acute disseminating encephalomyelitis with and without antibodies to the myelin oligodendrocyte glycoprotein. Issue 3 (13th August 2014) - Baumann, M; Sahin, K; Lechner, C; Hennes, E M; Schanda, K; Mader, S; Karenfort, M; Selch, C; Häusler, M; Eisenkölbl, A; Salandin, M; Gruber-Sedlmayr, U; et al.
Abstract : Background: Myelin oligodendrocyte glycoprotein (MOG) antibodies have been recently described in children with acute disseminating encephalomyelitis (ADEM), but the clinical and neuroradiological characterisation of this subgroup is lacking. Objective: To compare the clinical and neuroradiological features of paediatric ADEM with and without MOG antibodies. Methods: Clinical course, cerebrospinal fluid (CSF)-, MRI studies, outcome and MOG status of 33 paediatric ADEM prospectively studied were reviewed. Results: MOG antibodies (median 1:2560; range 1:160–1:20 480) were detected in 19 children with ADEM. The majority of children showed a decline of serum MOG-IgG titres over time. Children with MOG antibodies did not differ in their age at presentation, sex ratio, the presence of oligoclonal bands, clinical symptoms or initial severity, apart from a higher CSF cell count (p=0.038), compared with children without MOG antibodies. In addition, further relapsing demyelinating episodes associated with MOG antibodies were observed only in children with MOG antibodies. All 19 children with MOG antibodies had a uniform MRI pattern, characterised by large, hazy and bilateral lesions and the absence of atypical MRI features (eg, mainly small lesions, well-defined lesions), which was significantly different compared to that of children without MOG antibodies (p=0.003; and p=0.032, respectively). In addition, children with MOG antibodies had involvement of more anatomical areas (p=0.035) including the myelon characterised by a longitudinally extensive transverse myelitis (p=0.003), more often a complete resolution of lesions (p=0.036) and a better outcome (p=0.038). Conclusions: Patients with ADEM with MOG antibodies in our cohort had a uniform MRI characterised by large, bilateral and widespread lesions with an increased frequency of longitudinal extensive transverse myelitis and a favourable clinical outcome in contrast to children lacking MOG antibodies.